Biodiversidade como tema para a educação ambiental : contextos urbanos, sentidos atribuídos e possibilidades na perspectiva de uma educação ambiental crítica - Thiemann, Flávia Torreão Corrêa da Silva (Universidade Federal de São Carlos, 2013)
Biodiversity is all around us, in what we wear, eat, into objects from our daily, past and future lives. It is present as an explosion of colors and hues, sounds and smells. It is both invisible and inescapable. The discourses on biodiversity are also multiple: it is the basis of life on Earth, it is essential, and yet suffers constant threats. In this thesis we seek to raise possibilities of working with biodiversity as a theme in an urban environment, the São Carlos Ecological Pole, and to understand the meanings attributed to biodiversity by researchers and students in the Life Sciences and similar areas, and to envision possibilities for addressing the concept of biodiversity in environmental education processes conducted within the principles of a critical environmental education. We conducted a qualitative study, using naturalist research techniques and the Delphi Method, and used a philosophical hermeneutics perspective to interpret and understand the data. This research generated nine categories of meaning attributed to biodiversity: Concreteness, Symbolic, Knowledge, Holism, Kaleidoscope, Hidden, Threatened, Inclusive and Exclusive, listed 16 sets of concepts considered essential, organized in spheres that contemplate aspects of scientific content, values and action, and six suggestions of themes that can help the process of learning about biodiversity: Experiencing biodiversity; "Opening your eyes" for biodiversity; Exercising dialogue/discussions; Acknowledging the importance of biodiversity and the limits of human interference; Biodiversity in our own territory; Overcoming teaching fragmentation. The results are ideas, suggestions, possibilities to be explored from the perspective of a critical environmental education, and must be contextualized in processes that respect the multiplicity of views on environmental issues, and seek understanding and to build agreements that allow for action in favor of the diversity of life on Earth.
Keywords: Educação ambiental; Educação ambiental crítica; Polo Ecológico de São Carlos; Perspectiva hermenêutica; Ecologia; Biodiversidade; Ambiente urbano; Biodiversity; Critical environmental education; São Carlos Ecological Pole; Urban environment; Hermeneutics perspective; CIENCIAS BIOLOGICAS::ECOLOGIA